Equivalent stimuli for stripes in rats with striate cortex ablations. - Weiskrantz, L; Passingham, C (1975)
The purpose of the experiment was to determine which features of a visual discrimination task were used by rats with total striate cortex ablations. The task was vertical black and white stripes versus grey matched in flux. Probe trials were inserted in which stripes of two different orientations or a speckled pattern were substituted for either the positive or negative stimulus. It was found that the destriated rats were normal in response to stripes of different orientations, but showed a deficit with the speckled pattern. A finer analysis suggests that the latter finding reflected an increased preference for the speckled pattern by the destriated group.